Self-monitoring of Blood Glucose (SMBG): Cornerstone of Diabetes Management- Bangladesh Perspective: A Recommendation - Latif, Zafar Ahmed (Journal of Bangladesh College of Physicians and Surgeons, 2015)
SMBG is a crucial factor in diabetes management. It offersa quick check of glycemic status, helps to identify hypoglycemia and hyperglycemia. In addition SMBG assists in clinical decision making and as such it complements HbA1c. But due to many reasons SMBG is not practiced properly and adequately. In recent years several international guidelines higllighted the importance of SMBG for diabetes management. Very few diabetic patients in Bangladesh actually perform SMBG regularly at home. The awareness of the benefits of SMBG is also low. There is no uniformity in SMBG practice among the patients as there is no local guideline to help the physicians in determining the optimum SMBG frequency for their patients. So a working guideline on SMBG is the call of the day. This article is an attempt in that direction. Exploring international guidelines and evaluating their applicability in local context a number of recommendations have been proposed. J Bangladesh Coll Phys Surg 2014; 32: 218-223